An Improved Transformation System for Phytophthora cinnamomi Using Green Fluorescent Protein - Dai, Tingting; Xu, Yue; Yang, Xiao; Jiao, Binbin; Qiu, Min; Xue, Junxin; Arredondo, Felipe; Tyler, Brett M. (Frontiers in Microbiology, 2021)
Phytophthora cinnamomi is a destructive pathogen causing root rot and dieback diseases on hundreds of economically and ecologically important plant species. Effective transformation systems predispose modifications of candidate genes to understand the pathogenesis of P. cinnamomi. A previous study reported a polyethylene glycol and calcium dichloride (PEG/CaCl2) mediated protoplast transformation method of P. cinnamomi. However, the virulence of the transformants was compromised. In this study, we selected ATCC 15400 as the suitable wild-type isolate for PEG/CaCl2 transformation using the green fluorescent protein after screening 11 P. cinnamomi isolates. Three transformants, namely PcGFP-1, PcGFP-3, and PcGFP-5 consistently displayed a green fluorescence in their hyphae, chlamydospores, and sporangia. The randomly selected transformant PcGFP-1 was as virulent as the wild-type isolate in causing hypocotyl lesions of lupins. Fluorescent hyphae and haustoria were observed intracellularly and intercellularly in lupin tissues inoculated with PcGFP-1 zoospores. The potential application of this improved transformation system for functional genomics studies of P. cinnamomi is discussed.